O ensino de inglês na cibercultura: a inclusão a partir de práticas multiletradas - Oliveira, Larissa Xavier de (2019)
The present study aimed to comparatively analyze the potential of BBC Learning English and Memrise platforms, in inclusive English teaching. This is a qualitativeinterpretative research (MINAYO, 2001) based in exploratory approach (GIL, 2016) which methodological-theoretical framework is anchored to the Bakhtinian dialogic language conception, to the second language acquisition theory (ELLIS, 2003; 2012), to the Computer-Assisted Language Learning theory (WARSCHAUER, 19O6; LEFFA, 2006), to multiliteracies (NEW LONDON GROUP, 2000; COPE; KALANTZIS, 2015), to the English use as a Língua Franca (JORDÃO, 2009; JENKINS, 2010; DUBOC 2014), to cyberculture concepts (LEMOS, 2007; JENKINS, 2010; RÜDIGER, 2013), to inclusive teaching (CAMPBELL, 2001; CERCHIARI, 2014; FRANÇA et al, 2016) and to the web accessibility parameters (BRASIL, 2014). For the analysis, we have built a matrix based on the evaluation parameters of educational websites proposed by Carvalho (2008) and on the English language acquisition context. The analysis steps ran through the evaluation matrix building, the exploration and development of a comparative study of BBC learning and Memrise platforms on the defined parameters. To the parameters building, the linguistic, methodological, and accessibility aspects in the websites were considered. After analyzing BBC Learning English and Memrise, we realized they are not in conformity to the web accessibility standards, also, they do not contemplate dialogical language acquisition and multiliteracies conceptions. Thus, both platforms do not show an inclusive English learning potential.